Exercise and the hepatic sirtuin network: rethinking the research focus on SIRT1, SIRT3, and SIRT6 - Kwon, Jun Woo (Frontiers in Physiology, 2026)
Exercise remains one of the most effective non-pharmacological strategies for improving non-alcoholic and metabolic-associated fatty liver disease (NAFLD/MASLD). Beyond its systemic effects, regular physical activity rewires hepatic energy metabolism and enhances mitochondrial efficiency. Within this adaptive process, members of the Sirtuin family-particularly SIRT1, SIRT3 and SIRT6-have received considerable attention. These proteins operate at distinct regulatory layers: SIRT1 modulates transcriptional programs, SIRT3 shapes mitochondrial metabolic fluxes, and SIRT6 influences chromatin architecture and epigenetic repression. Together, they are widely regarded as the principal molecular mediators linking exercise to improved hepatic metabolic function. However, the Sirtuin family consists of seven members, and accumulating evidence indicates that the remaining isoforms-SIRT2, SIRT4, SIRT5 and SIRT7-also participate in the hepatic response to exercise. Their potential roles include buffering metabolic stress, supporting protein quality control, and modulating inflammatory signaling, suggesting a broader regulatory network than currently emphasized. This Perspective revisits the exercise–Sirtuin axis from a mechanistic physiology standpoint. It examines why research focus has historically converged on SIRT1, SIRT3 and SIRT6, and considers emerging data implicating the full Sirtuin repertoire in exercise-induced metabolic remodeling. The argument put forward is that future work may benefit from a more integrated framework that views exercise not as a trigger for a few dominant pathways, but as a stimulus capable of reorganizing an interdependent Sirtuin network governing hepatic metabolic resilience. Collectively, these considerations prompt a shift from a single-axis understanding toward a distributed regulatory model of hepatic adaptation to exercise.